Bruteforce In The Hydra Process And Telnet Service Using The Naïve Bayes Method: Bruteforce In The Hydra Process And Telnet Service Using The Naïve Bayes Method - Tarisno Amijoyo; Rusydi Umar; Anton Yudhana (Institute of Computer Science (IOCS), 2020)
Internet technology is increasingly developing, in accordance with the needs of an increasingly millennial society. The growth of internet technology has been accompanied by an increasing variety of attack techniques aimed at the media. BruteForce is one of the techniques of attack (hacking) against the internet network by hacking passwords from users who are active or inactive at that time. Through a process with a small application such as Hydra accompanied by telnet service, then hacking techniques with BruteForce can be run, to attack an internet network. The Hydra process and the telnet service referred to in the study are those that included a